EFEKTIFITAS KAPSUL MENGKUDU (Morinda citrifolia) TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS DI RS BRAWIJAYA - Yuni Irianti; Ngadiani Ngadiani (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2017)
We report the supplementation of noni (Morinda citrifolia) to decrease blood sugar levels in patients with diabetes mellitus Brawijaya Hospital Surabaya, and noni problems whether supplementation is effective in reducing blood sugar levels in diabetes patients mellitus.The goal of this study was to determine the effectiveness of capsule morinda to decrease blood sugar levels in patients with Diabetes Mellitus in Brawijaya Hospital Surabaya. This type of research is to ekperimem quasi control group design with pre-test and post test. The population in this study are patients with diabetes mellitus in hospital outpatient Brawijaya. The sampling technique with a number of 60 people who were divided into 30 groups of control (can drug from a doctor) and 30 in the experimental group (can medicine from the doctor and consumption of noni capsules) .Instrumen this study is the laboratory results of random blood sugar levels with the tools glucometer ( gluko Dr). Data analysis was performed using univariate and bivariate (parametric test, Kolmogorov-Smirnov test z and Independent T-Test). From the results, no significant difference the difference in the results of pre-test and post-test in the control group and the experiment is p = 0.020 (<0.05), then the alternative hypothesis (Ha) is accepted (the results are meaningful). It is concluded that supplementation of noni effective in helping to decrease blood sugar levels of patients with diabetes mellitus, it is advisable to consume noni capsules and routine checks of blood sugar levels so that the blood sugar levels under control.